PENGARUH KOMITMEN ORGANISASI, BUDAYA ORGANISASI DAN KEPUASAN PENGGUNA SIMDA PADA KINERJA SATUAN KERJA PERANGKAT DAERAH - Adi, I Wayan Asdita; Sadha Suardikha, I Made; Dwija Putri, I G. A. M. Asri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
This study aims to know about the influence of organizational commitment, organizational culture and SIMDA user satisfaction on SKPD performance in the Government of Gianyar regency. Data collection used primary data collected using questionnaire techniques. All units of the Regional Device (SKPD) within the Government of Gianyar Regency became the study population. The technique of determining the sample using purposive sampling method. The number of samples in this study as many as 50 treasurer spending on all SKPD in Gianyar regency government. Data analysis technique used is multiple regression analysis. Before performing multiple regression analysis, first classical assumption testing is done. Furthermore, the model accuracy test is done by looking at the coefficient of determination (adjusted R2), model feasibility test (F test) and hypothesis test result (t-test). Based on the results of hypothesis testing showed that organizational commitment have a positive effect on SKPD performance, organizational culture has a positive effect on SKPD performance, user satisfaction has a positive effect on SKPD performance